Introducing carbon quantum dot-Capivasertib drug carrier complex for enhanced treatment of breast cancer - Moones Rahmandoust; Soroush Abdolrahimi (PLoS ONE, 2025)
Capivasertib (AZD5363) is a 2023 FDA-approved pyrrolopyrimidine-derived compound that treats hormone receptor positive, HER2 negative metastatic breast cancer in adult patients. It is a novel pan-AKT kinase catalytic inhibitor in ER + breast cancer cell lines, including MCF7. The dominant influence of carbon quantum dots (CQDs) in combination with multiple chemotherapy drugs is also demonstrated as a drug delivery system that significantly enhances the effectiveness of cancerous tumour treatments by providing reduced side-effects, through targeted delivery of the drug, controlled release, enhanced solubility, permeability and retention. In this study, the impact of the conjugation of AZD5363 drug to N-doped, S-doped, and N/S-doped CQDs was investigated on inducing apoptosis by inhibiting the AKT signalling pathway in the MCF7 cell line. Initially, hydrothermal and pyrolysis methods were used to construct CQDs. Then, the synthesized quantum dots were conjugated with AZD5363 at three different concentrations, i.e., 0.03, 0.3, and 3nM. The MTT test results, on MCF7 cells, showed that although all the studied CQDs were biocompatible, the complex of N/S-doped CQD-AZD5363 at a concentration of 0.03nM was the most effective. After obtaining immunocytochemistry results, flow cytometry and cell invasion tests were employed to demonstrate the high potential of the introduced drug carrier complex in reducing AKT protein expression, induction of apoptosis and prevention of cell metastasis and invasion. According to these results, the binding of N/S-doped CQD to AZD5363 increases the effectiveness of this drug, with reducing the IC50 concentration, and more specificity to cancerous cells, introducing it as a suitable candidate for the treatment of breast cancer.